Visual Diagnosis: Pediatric Airway Emergency. (27th March 2012) - Desai, Bobby; Beattie, Lars; Ryan, Matthew F.; Falgiani, Michael
Abstract : We present a case of a potentially difficult airway emergency in a pediatric patient. After presentation, we briefly review critical differences between pediatric and adult airways and management of the airway during these emergencies.